PERBANDINGAN SIFAT IMPAK DAN KETAHANAN API KOMPOSIT BERPENGUAT SERAT ALAM DENGAN FILLER BENTONITE CLAY - Kaleb Priyanto; Andika Wibowo; Roy Tarigan; Ridwan Afandi (Jurnal Pendidikan Teknik Mesin, 2025)
This research presents a comparative study on the impact strength and combustion resistance of polyester matrix composites reinforced with natural fibers and bentonite filler. Two types of natural fibers—pineapple leaf fiber and sansevieria fiber—were used as reinforcement, with 5% bentonite added as filler in each composite variation. Impact testing was conducted in accordance with ASTM D-4812-99, while combustion resistance was evaluated based on ASTM D-635. The results indicate that the composite reinforced with pineapple leaf fiber exhibited higher impact strength than that reinforced with sansevieria fiber, with the highest value recorded at 0.79 J/mm² for the N50B5 variation. The addition of up to 5% bentonite significantly enhanced both impact strength and combustion resistance. The S50B5 variation showed the best fire resistance performance, with a Time to Ignition (TTI) of 10.87 seconds and a Rate of Burning (ROB) of 11.63 mm/min. This improvement in combustion resistance is attributed to bentonite’s role as a filler that reduces oxygen penetration by filling gaps within the matrix and forming a protective barrier against heat. Thus, the addition of bentonite up to 5% can improve the mechanical properties and thermal resistance of polyester-based composites, and make them superior for applications that require fire and impact resistance.